2013
DOI: 10.1523/jneurosci.5816-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Dissociable Mechanisms of Self-Control: Early Attentional Filtering Versus Late Value Modulation

Abstract: Optimal decision-making often requires exercising self-control. A growing fMRI literature has implicated the dorsolateral prefrontal cortex (dlPFC) in successful self-control, but due to the limitations inherent in BOLD measures of brain activity, the neurocomputational role of this region has not been resolved. Here we exploit the high temporal resolution and whole-brain coverage of event-related potentials (ERPs) to test the hypothesis that dlPFC affects dietary self-control through two different mechanisms:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
134
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(149 citation statements)
references
References 76 publications
(10 reference statements)
13
134
1
1
Order By: Relevance
“…In addition to the altered coupling between vmPFC and Amyg/vStr, we identified a second signaling pathway between vmPFC and dlPFC that showed a reduction in negative connectivity for participants with high PSL. Prior work (Hare et al, 2009;Harris et al, 2013) suggests that this dlPFC-vmPFC connection may help to modulate value comparisons and to integrate taste and health attributes in the vmPFC. A weaker modulatory connection with dlPFC might result in less effective downregulation of the impact of the taste signaling, resulting in a relative weighting for taste attributes in vmPFC that is too high given the health goal.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the altered coupling between vmPFC and Amyg/vStr, we identified a second signaling pathway between vmPFC and dlPFC that showed a reduction in negative connectivity for participants with high PSL. Prior work (Hare et al, 2009;Harris et al, 2013) suggests that this dlPFC-vmPFC connection may help to modulate value comparisons and to integrate taste and health attributes in the vmPFC. A weaker modulatory connection with dlPFC might result in less effective downregulation of the impact of the taste signaling, resulting in a relative weighting for taste attributes in vmPFC that is too high given the health goal.…”
Section: Discussionmentioning
confidence: 99%
“…Middle-to-posterior insular regions are further related to the exertion of self-control over food intake (Harris et al, 2013) and the integration of interoceptive sensations (Craig, 2002). Due to its high connectivity with the dlPFC and the vmPFC (Carmichael and Price, 1996;Craig, 2002), the insula is thought to be a key player enabling the interactions between regions for stimulus valuation and choice (Harris et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Middle-to-posterior insular regions are further related to the exertion of self-control over food intake (Harris et al, 2013) and the integration of interoceptive sensations (Craig, 2002). Due to its high connectivity with the dlPFC and the vmPFC (Carmichael and Price, 1996;Craig, 2002), the insula is thought to be a key player enabling the interactions between regions for stimulus valuation and choice (Harris et al, 2013). Prior electrical neuroimaging studies have further shown that insular activity is elevated within 150ms when participants view meal portion sizes judged as inappropriate for prospective intake (Toepel et al, 2015) further indicating its role in the integration of homeostatic and hedonic information.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the perceived stress level (but in turn not the cortisol reaction) was associated with the connectivity strength between left dorsolateral prefrontal cortex (dlPFC) and the vmPFC: the more stressed participants had felt, the weaker was the connectivity between these two regions when self-control was needed to overcome taste temptations in order to choose the healthier food. A series of studies have demonstrated that connectivity between dlPFC and vmPFC relates to the degree to which individuals use self-control in dietary choice (89)(90)(91)(92). This connection in the prefrontal cortex may server to maintain a goal context that promotes focusing on long-term outcomes such as future health, whereas sensory and motivational signalling from subcortical areas may promote information about more immediate choice outcomes.…”
Section: How Physiological Psychological and Emotional Factors Predmentioning
confidence: 99%